Generation of grid multiscroll chaotic attractors using current conveyor - Lin, Y.; Wang, C.H.; Xu, H. (Нелінійні коливання, 2013)
We study the chaos in a system of three differential equations with piecewise linear right-hand sides, and numerically find chaotic attractors in the system, together with experimentally corresponding modes in an electrical circuit. Вивчено хаос у системi трьох диференцiальних рiвнянь з кусково-лiнiйною правою частиною та чисельно знайдено хаотичнi атрактори системи разом з експериментально вiдповiдними режимами електричної схеми.